Fabrication of a room-temperature NO2 gas sensor using morphology controlled CVD-grown tellurium nanostructures - Choi, Ik Jun; Kim, Bum Jun; Lee, Sang Hoon; Jeong, Byung Joo; Nasir, Tuqeer; Cho, Yun Seong; Kim, Noeul; Lee, Jae Hyun; Yu, Hak Ki; Choi, Jae Young (Sensors and Actuators, B: Chemical, 2021)
A room-temperature (∼26 °C) NO2 gas sensor was fabricated using tellurium (Te) nanostructures. Te forms a helical chain with strong covalent bonds in the c-axis and weak van der Waals bonds between the chains. Therefore, the energy required for gas adsorption and desorption is low, thus, giving it the advantage of operating at room temperature. Since the shape and size of the Te helical chains can be freely controlled by adjusting the growth parameters, the electrical reactivities of Te to a specific gas can be controlled. In this study, the reactivity of Te to NO2 gas was controlled by adjusting the number of Te nanotube walls and lengths. It was also verified that the gas detection performance was maintained even with increasing humidity.
Keywords: Adsorption and desorptions; Growth parameters; Helical chains; Morphology-controlled; Nanotube walls; NO2 gas sensor; Shape and size; Van der Waals bonds; NO2 gas sensor; Room temperature gas sensors; Tellurium nanostructures